Thorough design and pre-trial quality assurance (QA) decrease dosimetric impact of delineation and dose planning variability in the STRICTLUNG and STARLUNG trials for stereotactic body radiotherapy (SBRT) of central and ultra-central lung tumours. (June 2022) - Hoffmann, L.; Persson, G.F.; Nygård, L.; Nielsen, T.B.; Borrisova, S.; Gaard-Petersen, F.; Josipovic, M.; Khalil, A.A.; Kjeldsen, R.; Knap, M.M.; Kristiansen, C.; Møller, D.S.; et al.
Highlights: Report on an extensive QA-programme for an SBRT trial for central lung tumours. Small variations in OAR delineation potentially leads to large OAR over-dosage. Extensive QA decreases variability in OAR delineation and treatment planning. QA of OAR delineations may lead to a more coherent interpretation of trial outcome. Abstract: Introduction: SBRT of central lung tumours implies significant risk of toxicity. We are initiating two phase II trials prescribing 56 Gy/eight fractions to PTV, allowing for dose escalation of GTV. We prioritize organs at risk (OAR) constraints over target coverage, making the treatment plans very sensitive to OAR delineation variations. The aim of this study is to quantify the dosimetric impact of contouring variations and to provide a thorough description of pre-trial quality assurance to be used in upcoming trials to provide consistent clinical care. Materials and methods: Delineation: Seven physicians delineated OAR in three rounds, with evaluations in-between. For each patient case, seven treatment plans, repeatedly using each of the OAR structure sets from the seven physicians, were made and compared to evaluate the dosimetric effect of delineation variability. Treatment planning: Treatment plans for seven cases were made at six departments in two rounds, with discussion in-between. Results: OAR delineation variation between centres resulted in high variabilities in OAR dose for simulated plans and led to potential overdosage of the lobar bronchus (constraint: D0.03cc  < 45 Gy), with maximum doses ranging between 58 Gy (first round), and 50 Gy (third round). For mediastinal tissue, the constraint (D0.03cc  < 45 Gy) was violated for the majority of the delineations in all three rounds, with maximum doses of 84 Gy (first round), and 72 Gy (third round). For the treatment planning study, the range of the standard deviation for GTV mean dose was 12.8–18.5 Gy (first round) and 2.8–3.5 Gy (second round). Conclusions: Even small variations in OAR delineation led to high OAR overdosage. The study demonstrates the importance of having extensive QA procedures in place before initiating clinical trials on dose escalation in SBRT.